Peralihan Hak Atas Tanah melalui Hibah Secara Lisan: Studi Kasus Putusan Pengadilan - Dian Ayu Meika Putri; Ana Silviana (SIGn Jurnal Hukum, 2022)
This study aims to examine and analyze the cancellation of the transfer of land rights through oral grants. In addition, to understand the legal consequences of Decision No. 30/Pdt.G/2020/PN.Tnr regarding the position of the land object obtained against the law. This study uses a normative juridical research method. The data was collected using literature study techniques on primary, secondary, and tertiary legal materials. The collected legal material is then analyzed using qualitative data analysis methods with a statute approach and a case approach which will then conclude the object of the research. The results show that the transfer of land rights is implemented through oral grants in Decision No. 30/Pdt.G/2020/PN.Tnr is invalid and null by law. In this case, based on Article 617, Article 1320, Article 1335, Article 1365, Article 1682, and Article 1688 point 2 of the Civil Code. In addition, there are rules and prohibitions for transferring land from the distribution of the Transmigration Program. While the legal consequences are defendants, I to VIII and co-defendant V must vacate and get out from the land right of ownership plaintiff in excellent and intact condition. Therefore, it is recommended that each party that implements the grant knows the rules according to the applicable laws and regulations. Meanwhile, the recipient of the distribution of Land from the Transmigration Program must understand the rules and prohibitions as a participant in the program. The government and related agencies must be more intense in socializing with the public about the importance of making a grant deed before the Land Deed Official. This condition aims to minimize the occurrence of land disputes in the future due to oral grants.